Association of Relative Handgrip Strength With Anthropometric Measures and Lipid Profiles in Individuals With Cardiovascular Disease: Results From RaNCD Cohort Study. Issue 4 (October 2021) - Pasdar, Yahya; Khamoushi, Firoozeh; Rezaeian, Shahab; Darbandi, Mitra; Najafi, Farid; Hamzeh, Behrooz
Abstract : The present study was conducted to assess the relationship between relative handgrip strength (RHGS) and cardiovascular risk factors in individuals with cardiovascular disease (CVD) and healthy subjects. This study was based on a cross-sectional analysis of 883 participants aged 35 to 65 years among those with CVD and healthy subjects from Ravansar Non-Communicable Disease (RaNCD) cohort study. There was a significant inverse association between body fat percentage, body fat mass, waist circumference, hip circumference, and waist-to-hip ratio with RHGS in both groups ( P < .001). There was no significant association between RHGS and total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein of the 2 groups ( P > .05). Increased RHGS may be associated with improved body composition in individuals with CVD and individuals with no CVD, which requires further longitudinal studies.